Reusability performance of zinc oxide nanoparticles for photocatalytic degradation of POME - Zainuri, Nur Zarifah; Hairom, Nur Hanis Hayati; Abu Bakar Sidik, Dilaelyana; Misdan, Nurasyikin; Yusof, Norhaniza; Mohammad, Abdul Wahab (EDP Open, 2018)
Performance and reusability of different zinc oxide nanoparticles (ZnO-PVP and ZnO-PEG) for photocatalytic degradation of palm-mill oil effluent (POME) has been studied. The nanoparticles properties were haracterised with fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The TEM results show that ZnO-PEG nanoparticles exhibit the smaller size than ZnO-PVP with less agglomeration. It was found that ZnO-PEG shows better effectiveness than ZnO-PVP in reducing turbidity, colour and increasing the dissolved oxygen (DO). By using two types of reusability methods: (a) oven drying (b) hot water rinsing, the oven drying method portrayed the most efficient route for POME treatment. This research would be a solution to the palm oil industry for photocatalyst recovering as well as reduction of the chemical usage in order to meet the development of advanced and greener technologies.